Optimal foraging strategies in varying nutrient heterogeneity: responses of a stoloniferous clonal plant to patch pattern, size and quality. Issue 3 (3rd July 2022) - Zheng, Xiaona; Gao, Yang; Wang, Yanan; Xing, Fu; Zhao, Meixuan; Gao, Ying
ABSTRACT: Contrast and aggregation are two components of spatial heterogeneity. To precisely determine the influence of varying nutrient heterogeneity on the foraging behavior of clonal plants, we selected Potentilla anserina L. as the material and designed different patch patterns, sizes and qualities. In Experiment 1, compared with random and uniform patch patterns, aggregation increased ramet density and biomass accumulation at the patch scale, but not at the plot scale. This implies that the adaptive responses of clonal plants to nutrient heterogeneity depend on spatial scale. We further designed three levels of patch size with the same fertilizer concentration at the patch scale in Experiment 2, and four levels of patch quality with the same total amount of fertilizer at the plot scale in Experiment 3. Increased ramet density and stolon growth rate within small patches in Experiment 2 demonstrated effects of heterogeneity on plant foraging responses at the patch scale, while no difference was found in Experiment 3. This means that the influence of patch size on ramet establishment and residence time was alleviated by patch contrast at larger spatial scales. Hence, spatial scale is a key factor determining the interactions between heterogeneous ecosystem components.